DEVELOPING SPEAKING SKILLS AT HIGH SCHOOL THROUGH THE IMPLEMENTATION OF FLIPPED LEARNING PRACTICES (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article focuses on the positive effects of the flipped learning methodology on high school learners .Flipped learning is a learner-centred approach that forms part of blended learning and makes use of technological developments in education.Data were collected from high school students who were using flipped learning methodology. The study's findings focus on the effectiveness of the researcher-prepared flipped learning procedures.The results demonstrate the relevance of flipped learning in developing English-speaking skills in line with Common European Framework Reference (CEFR) levels.